2022
DOI: 10.1088/1755-1315/1045/1/012128
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of balanced development of the agro-industrial complex in the regional aspect

Abstract: The article examines the current level of the agro-industrial complex of the South of the Tyumen region. The main problems hindering the development of the industry are identified. Prospects and mechanisms of influence on the balanced development of the agro-industrial complex are revealed. The authors describe and give arguments for the positive impact of the balanced development of the agro-industrial complex on the economic component of the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These included an increase in the availability of the number of receptors for ADP and adrenaline on the surface of heifer platelets, an increase in the number of fibrinogen receptors (GPIIb-IIIa) on them, and an increase in platelet phospholipase A 2 , which releases arachidonic acid from membrane lipids for its conversion into thromboxane A 2 [12]. Found some acceleration in the development of platelet aggregation in the case of the simultaneous use of two or three stimulators of this process, said that heifers that were tethered during their rearing had an age-related increase in their mutually reinforcing effects on platelets [13]. The tendency to increase the intravascular activity of platelets, which was revealed in heifers kept in tether during rearing, confirmed the activation of all these mechanisms under blood flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These included an increase in the availability of the number of receptors for ADP and adrenaline on the surface of heifer platelets, an increase in the number of fibrinogen receptors (GPIIb-IIIa) on them, and an increase in platelet phospholipase A 2 , which releases arachidonic acid from membrane lipids for its conversion into thromboxane A 2 [12]. Found some acceleration in the development of platelet aggregation in the case of the simultaneous use of two or three stimulators of this process, said that heifers that were tethered during their rearing had an age-related increase in their mutually reinforcing effects on platelets [13]. The tendency to increase the intravascular activity of platelets, which was revealed in heifers kept in tether during rearing, confirmed the activation of all these mechanisms under blood flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the study, it turned out that highly mineralized sulfide continental silt (the same therapeutic mud) is a cure for many diseases: from psoriasis to infertility. For a decent and official treatment of many diseases, we propose to build a sanatorium-resort facility [4].…”
Section: Methodsmentioning
confidence: 99%
“…From all of the above, it can be concluded that the Aromashevsky municipal district has the necessary resources and infrastructure to accommodate the production of pellets and briquettes [8][9][10].…”
Section: Fig 2 Location Of the Engineering Structure Near The Object ...mentioning
confidence: 98%